Sustaining capacity for supplying evidence for agricultural & rural development policies - Adebayo, Kolawole; Rhoe, Valerie (International Food Policy Research Institute, 2008)
The Federal Government of Nigeria has demonstrated a strong commitment to achieving the Millennium Development Goals (MDGs) and the NEEDS Targets. Recognizing the importance of agriculture, as well as the challenges faced by the sector, in providing evidence for policymaking, the Federal Ministry of Agriculture and Water Resources (FMAWR) established the Agricultural Policy Support Facility (APSF), with the International Food Policy Research Institution (IFPRI) as its implementing partner and the Canadian International Development Agency (CIDA) providing financial support. APSF aims to strengthen the capacity of FMAWR to design and implement agricultural policies by addressing the fundamental knowledge, capacity, and communication problems faced by the Government of Nigeria. In order to support evidence-based policymaking, it is essential to identify the current capacity within Nigeria for providing evidence for policymaking and for creating this capacity for future generations. In collaboration with the University of Ibadan, University of Agriculture-Abeokuta, FMAWR, and IFPRI, a consultation workshop on “Sustaining Capacity for Supplying Evidence for Agricultural Rural Development Policies and Strategies was held at the University of Ibadan on April 28, 2008. The objectives of this consultative workshop were to identify: specific capacity challenges confronting university professors who are teaching the next generation of policymakers, policy analysts, researchers and university professors; curriculum gaps within the university programs for building capacity for designing and implementing pro-poor, gender sensitive, and environmentally sustainable agricultural and rural development policies and strategies; employment opportunities for the university graduates in agricultural economics and extension and the required skills; existing capacity for undertaking agriculture and rural development policy research; and current methods used by researchers to convey their results to decisionmakers and other stakeholders.